2014
DOI: 10.1163/15685411-00002835
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal assignment of oil radish resistance to Meloidogyne incognita and M. javanica using a set of disomic rapeseed-radish chromosome addition lines

Abstract: Root-knot nematodes cause severe damage to a great number of crops worldwide. The use of nematicides is restricted due to environmental and toxicological risks and control of the pest by crop rotation is difficult because root-knot nematodes have a very wide range of host plants. To verify the strategy of converting rapeseed from a tolerant host for Meloidogyne incognita and M. javanica to a resistant catch crop, a complete set of nine disomic rapeseed-radish chromosome addition lines (lines A to I) was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…WRKY transcription factor plays an important role in regulating plant growth and development and responding to various environmental stresses [23]. The functions of WRKY transcription factors in rapeseed were mainly studied by constructing overexpression vectors and CRISPR/Cas9 gene editing vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WRKY transcription factor plays an important role in regulating plant growth and development and responding to various environmental stresses [23]. The functions of WRKY transcription factors in rapeseed were mainly studied by constructing overexpression vectors and CRISPR/Cas9 gene editing vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al [24] overexpressed BnWRKY149 and BnWRKY217, Copyright © Shaosong Zhang MCDA.000804. 13(1).2023 which proved that BnWRKY149 and BnWRKY217 played an important role in the resistance to abiotic stress ABA [23]. Cui et al [25] found that the overexpression of phosphate BnaWSR1 (BnaWSR1ca) in rapeseed protoplasts triggered the production of Reactive Oxygen Species (ROS) and cell death, while its ectopic expression in Arabidopsis increased the levels of salicylic acid (SA) and ROS, thus accelerating leaf senescence.…”
Section: Discussionmentioning
confidence: 99%